Mechanism of the electron-exchange reactions between mixed ligand Fe(III) complexes and cyano complex of Fe(II) - Khattak, Rozina; Khan, Muhammad Sufaid [UNESP]; Naqvi, Iftikhar Imam (My University, 2018)
Our interest was to study the reactions of those mixed ligand complexes of Fe(III), where cyanide plays its role as a ligand. We synthesized the mixed ligand complexes of Fe(III) with diimine and cyanide as ligands to form octahedral geometry with high stability. We adopted previously cited procedures with improvements. The synthesized complexes, [FeIII(phen/bpy)2(CN)2]+ were reduced by the hexacyano complex of Fe(II) that is well-known for its high stability and octahedral geometry. The reduction was performed in aqueous medium at constant ionic strength of 0.06. The progress of the reactions was monitored spectrophotometrically by measuring the formation of [FeII(phen/bpy)2(CN)2], i.e., the increase in absorbance with time. We found that the reduction of the mixed ligand Fe(III) complexes takes place in two phases. The first phase, when the Fe(III) complex is reduced to the neutral Fe(II) complex followsing zeroth order kinetics. The second phase was observed to be the rate-determining or slow step in the reduction of each complex, and the electron-exchange took place by an overall second order kinetics. In order to refine our results and to differentiate between the species which were taking part in the rate-determining step (slow step) and those which were taking part in the fast step, we studied the effect of protons and ionic strength on the rate constants in aqueous medium. We proposed an outer-sphere mechanism for the electron-exchange between Fe(III) and Fe(II) complexes.
Keywords: Dicyanobis(bpy)iron(III); Dicyanobis(phen)iron(III); Hexacyanoferrate(II)